Corn Cob (Zea Mays L.) Bricket with the Addition of Lemongrass (Cymbopogon Nardus L.) as a Natural Mosquito Repellent - Ahmadan Ilham Maulana; Elnino Profetika Zarathrustra; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2022)
Various alternative materials have been found and utilized by the community, such as biogas and biomass. One of them that has been used is briquettes. The purpose of this study was to determine the manufacturing process and advantages of corn waste briquettes with the addition of lemongrass. This type of research is a combination of descriptive research with literature review. The focus of the research description is the manufacture of mosquito repellent briquettes and strengthened by analysis of literature studies to analyze the content of lemongrass which can repel mosquitoes. This research is the result of observations on the manufacture of corncob briquettes (Zea Mays L.) combined with the addition of lemongrass (Cymbopogon Nardus L.) with the aim of providing added value to the briquettes, that can also be used to repel mosquitoes. Analysis of the use is that each combustion produces carbon dioxide. By taking advantage of the nature of gas particles whose shape and volume are always changing, researchers add value to the results of the combustion. Thus, the carbon dioxide produced contains active substances contained in lemongrass, namely citronellal, geraniol, and silica from combustion. Silica is toxic when it hits insects (mosquitoes) and can cause death because mosquitoes will lose fluids continuously (dehydration). The aroma of briquette smoke can be used as aroma therapy. Another great benefit is that it can teach the community about making briquettes which can also be used as mosquito repellent.